2012
DOI: 10.1007/s00604-012-0795-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-step electrochemical fabrication of a non-enzymatic glucose-selective glassy carbon electrode modified with copper nanoparticles and graphene

Abstract: We have developed a non-enzymatic glucose sensor by using a composite prepared from copper nanoparticles (CuNPs) and graphene which can be prepared by simple 1-step electrochemical reduction using graphene oxide (GO) and copper ion as the starting materials. The GO is electrochemically reduced to graphene at a voltage of −1.5 V, and this is accompanied by the simultaneous formation of CuNPs on the surface of the graphene. This novel nanocomposite combines the advantages of graphene and of CuNPs and displays go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…For enzyme-free glucose sensing, non-noble metals such as Cu and Ni have been widely studied as the anodes of glucose oxidation in alkaline media [2]. Many research efforts are focused on preparing Cu nanoparticles (NPs) or nanocomposites, such as Cu NPs/GR [3], Cu-CuO NWs [4], CuNWs [5], Cu foam [6], CuO/rGO [7], Cu/porous silicon [8], CuO nanoleaf/ZnO nanorods [9], and Cu 2 O/NiO x /GO [10].…”
Section: Introductionmentioning
confidence: 99%
“…For enzyme-free glucose sensing, non-noble metals such as Cu and Ni have been widely studied as the anodes of glucose oxidation in alkaline media [2]. Many research efforts are focused on preparing Cu nanoparticles (NPs) or nanocomposites, such as Cu NPs/GR [3], Cu-CuO NWs [4], CuNWs [5], Cu foam [6], CuO/rGO [7], Cu/porous silicon [8], CuO nanoleaf/ZnO nanorods [9], and Cu 2 O/NiO x /GO [10].…”
Section: Introductionmentioning
confidence: 99%
“…3.0 × 10 -2 µM (S/N=3), which was lower than that of CuNPs-GR/GCE [42,43]. The reason was that the introduction of PMo 12 , which was efficient for the uniform growth of CuNPs and electron transport.…”
Section: Amperometric Detection Of Glucosementioning
confidence: 72%
“…2(C). The bands associated at $1328, $1600, 2677 and 2922 cm À1 correspond to D (defect band due to intervalley scattering), G (graphene band), 2D and D + G bands, respectively [31][32][33]. After applying the potential of À0.7 V, it was observed that the intensity of the D and G bands is not reversed, once graphene oxide is not reduced to graphene.…”
Section: Fig 1(a) Shows Gce Without Modification Andmentioning
confidence: 91%